Um estudo de bases de Riesz e aplicação na controlabilidade fronteira para um sistema de equações de ondas acopladas - Primo, Shirley dos Santos (2023)
In this dissertation work, we will study the exact controllability for a system of coupled wave equations in the one-dimensional case with the control acting on the boundary of only one equation. To solve the controllability problem, we use the method of moments, which consists of transforming the control problem into a moment problem. The controllability of the system of equations and the problem of momentum are entirely related to the properties of the families of exponentials that arise naturally from the system, more precisely, it boils down to showing that such a family constitutes a Riesz basis.